Effective Burden of Business Taxation and Tax Eff ort of Local Governments - Axel von Schwerin (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper explores to what extent governments consider the effective tax burden of their tax policies. More specifically, the paper asks whether governments set higher statutory tax rates, if the effective tax burden on business is reduced. To address this question, the paper exploits an odd institution in the German federal income tax code, which substantially changed the effective tax burden of the local business tax. A federal tax reform enacted in 2008 made a large part of the business tax deductible from the federal income tax. This paper provides evidence that this implicit subsidy has drastic effects on local tax effort. The empirical analysis exploits the fact the reform has created a quasi-experiment, as the tax burden is treated only below a certain threshold, thus creating a kink point in the public budget constraint. By now, more than 10% of German municipalities have set local tax rates identical to this threshold level, causing excess bunching within the tax rate distribution of more than 10,000 local governments. Using this phenomenon, I will be able to estimate the elasticity of the tax base.
Keywords: H71; H23; H25; 330